Judicial System of the Uzbek SSR in the 60-70s of the XX Century - Komolov Dilshod Pulatovich (Genius Journals, 2022)
This article describes the changes that occurred in the history of the judicial system of the Uzbek SSR in the 60s and 70s of the 20th century. In particular, after the death of Stalin, the implementation of liberal reforms in the judicial system, the abandonment of the centralization policy, the increase of powers of the allied republics in the judicial sphere, the holding of elections in the judicial system, and the national composition of judges are given. Also, the suppression of the best and most educated personnel who think independently and protect national interests in the judicial system by the Soviet authorities in the 70s of the 20th century is highlighted
Keywords: Supreme court; regional court; district court; city court